REPRESENTATIONS OF PHYSICAL EDUCATION CLASSES UNDER THE VIEWPOINT OF PUPILS IFAL PALMEIRA DOS ÍNDIOS (Fiep Bulletin - online, 2013)
Physical Education is a segment of human sciences that faces many problems as it is often represented as a discipline that does not contribute directly to the intellectual development of the person. This is misinterpreted because teaching sports is part of the contents of PE and sports can be learned on the streets or in specific schools. In high school the problem is bigger because many teachers do not know what content to teach. Students of IFAL, in Palmeira dos Indios Campus, were interviewed in order to interpret their representations of physical education, developing a pedagogical proposal. As a result it was found that they represent PE as a means of improving health and quality of life, especially for the men. There was no need to create a new curriculum, as the students felt motivated and satisfied with the contents that they learned, but there needs to be a change in the methodology of some classes, to appeal more to the students.
Keywords: physical education; high school; social representations